2016
DOI: 10.1021/acsami.6b11849
|View full text |Cite
|
Sign up to set email alerts
|

Photoactive/Passive Molecular Glass Blends: An Efficient Strategy to Optimize Azomaterials for Surface Relief Grating Inscription

Abstract: Irradiation of azomaterials causes various photophysical and photomechanical effects that can be exploited for the preparation of functional materials such as surface relief gratings (SRGs). Herein, we develop and apply an efficient strategy to optimize the SRG inscription process by decoupling, for the first time, the important effects of the azo content and glass transition temperature (T). We prepare blends of a photoactive molecular glass functionalized with the azo Disperse Red 1 (gDR1) with a series of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…[65] Recently, we have used PM-IRSAS to elucidate the T g dependence of photoorientation by mixing a DR1-containing molecular glass with various photopassive glasses. [73] We showed that the maximum orientation and the orientation stability, after the laser source is removed, are unaffected by the fraction of photoactive glass in the mixture at constant T g . The orientation and orientation stability both increase with T g up to an optimal value (60 °C for blends containing 40% of the photoactive glass) and then decrease and become constant, respectively, with further increase in the T g , which helps explain the complex T g dependence during the optical inscription of surface relief gratings.…”
Section: Photo-orientation Of Azobenzenes and Photocontrol Of Passivementioning
confidence: 80%
See 2 more Smart Citations
“…[65] Recently, we have used PM-IRSAS to elucidate the T g dependence of photoorientation by mixing a DR1-containing molecular glass with various photopassive glasses. [73] We showed that the maximum orientation and the orientation stability, after the laser source is removed, are unaffected by the fraction of photoactive glass in the mixture at constant T g . The orientation and orientation stability both increase with T g up to an optimal value (60 °C for blends containing 40% of the photoactive glass) and then decrease and become constant, respectively, with further increase in the T g , which helps explain the complex T g dependence during the optical inscription of surface relief gratings.…”
Section: Photo-orientation Of Azobenzenes and Photocontrol Of Passivementioning
confidence: 80%
“…For dispersed mixtures of the small molecule DR1 in different (isotactic, syndiotactic, and atactic) poly(methyl methacrylate)s, it was shown that the host polymer with the lowest glass transition temperature ( T g ) (60 °C) allowed the greatest DR1 mobility and thus the highest photo‐orientation . Recently, we have used PM‐IRSAS to elucidate the T g dependence of photo‐orientation by mixing a DR1‐containing molecular glass with various photopassive glasses . We showed that the maximum orientation and the orientation stability, after the laser source is removed, are unaffected by the fraction of photoactive glass in the mixture at constant T g .…”
Section: Photo‐orientation Of Azobenzenes and Photocontrol Of Passivementioning
confidence: 99%
See 1 more Smart Citation
“…[18] Azobenzenes are among the most popular molecular photoswitches because of their ability to undergo a conformational change between two isomeric states when irradiated with UV or visible light. [25][26][27][28][29] When dealing with 2D light-responsive substrates, topographies can be instructed by a direct laser writing exposure of azopolymeric films previously spun on planar glass substrates. [25][26][27][28][29] When dealing with 2D light-responsive substrates, topographies can be instructed by a direct laser writing exposure of azopolymeric films previously spun on planar glass substrates.…”
Section: Doi: 101002/advs201801826mentioning
confidence: 99%
“…Polarized light can be readily used to probe the orientation, and anisotropy of molecular systems, including thin films, proteins, and self‐assembled monolayers . When combined with microscopy, polarized light measurements can yield critical information about the orientation of crystallographic axes in microstructures or enable the ability to map the distribution of anisotropic domains .…”
Section: Introductionmentioning
confidence: 99%